Adherence to Disease-Modifying Therapies at a Multiple Sclerosis Clinic: The Role of the Specialty Pharmacist. (October 2020) - Banks, Aimee M.; Peter, Megan E.; Holder, Genna M.; Jolly, Jacob A.; Markley, Brandon M.; Zuckerman, Scott L.; Choi, Leena; Nwosu, Sam; Zuckerman, Autumn D.
Background: Disease-modifying therapy (DMT) delays disease progression and improves quality of life for patients with multiple sclerosis (MS), but adherence to DMT is often suboptimal. Vanderbilt Specialty Pharmacy (VSP) embeds pharmacists within an outpatient MS clinic to provide medication management and address barriers to adherence. Objective: We evaluated rates and predictors of adherence to DMT among patients with MS at an integrated specialty pharmacy. Methods: We included patients with MS who filled ≥3 DMT prescriptions from VSP during the study period. Adherence was defined as medication possession ratio (MPR) or proportion of days covered (PDC) ≥0.8. Reasons for nonadherence were collected from pharmacy claims and electronic medical records. Results: The study included 653 patients. Average MPR and PDC were 0.93 and 0.94, respectively. Eighty-eight percent of patients achieved MPR ≥0.8; 89% achieved PDC ≥0.8. Using financial assistance and having $0 out-of-pocket cost were associated with higher odds of achieving MPR and PDC ≥0.8 ( P < .05). Of the 12% of patients who were nonadherent, most were unreachable for refills. Conclusions: Ensuring financial assistance and low out-of-pocket costs are associated with high adherence to DMT within an integrated specialty clinic, but more work is needed to address adherence in unreachable patients.